Hemangiopericytoma following allogeneic hematopoietic stem cell transplantation in a patient with primary plasma cell leukemia: the first case report and literature review - Shi, Yajun; Liang, Guohao; Zhang, Haiying; Wang, Yaqing; Han, Ying; Tong, Shenglian; Liang, Shunyu; Wang, Ying; Bai, Hai (Frontiers in Oncology, 2024)
BackgroundHemangiopericytoma (HPC) is a rare secondary tumor after allogeneic hematopoietic stem cell transplantation (allo-HSCT), which has not been reported in the literature. Herein, we reported a case of HPC after allo-HSCT.Case descriptionWe reported a case of a middle-aged female patient with primary plasma cell leukemia who presented lumbosacral pain and right lower limb pain and numbness on1684 days post-transplant. She underwent an MRI of the lumbar spine, which showed abnormal signal intensity in the spinal canal at the second through fifth lumbar spine vertebral levels. The patient was diagnosed with HPC based on a pathological biopsy of the diseased tissue in the spinal canal. Radiotherapy was administered to the lesion in the second through fifth lumbar vertebrae. The patient experienced less numbness and pain.ConclusionAccording to the literature, this is the first reported case of post-transplant HPC. Therefore, attention should be paid to secondary tumors after transplantation, especially rare tumors.